Bibliometric Analysis: Digital Literacy in Sharia Business - Karisma, Ayu (Raudhah Publisher, 2025)
The publication of scientific publications will continue to increase the number of publications every year, which shows that the development of science and knowledge is increasing. If a research topic experiences an increase in publications every year, it shows that the topic is interesting to research. Researchers need to know a topic that is always experiencing an increasing trend in order to conduct further research related to that topic, one way is by conducting bubliometric analysis. The purpose of this study is to examine the development of research trends related to the topic of digital literacy in Sharia business. The method used in this study is bibliometric analysis, data collection in the study is carried out by searching through Scopus with the keyword: